"A roof over my head": homeless women and the shelter industry - Williams, Jean Calterone, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Based upon extensive ethnographic data that examines lives of homeless women who care for children and live in small shelters and transitional living centers. This ground-breaking study unveils the centrality of abuse and poverty in homeless women's lives and outlines societal responses that should be more effective.--Provided by publisher.
A roof over my head: homeless women and the shelter industry
Causes of homelessness: homeless women speak -- Geography of the homeless shelter -- Homeless and battered women: parallel stories, opposing identities -- Meanings and myths of homelessness: housed people speak -- Meanings and myths of homelessness: homeless women speak.
Second edition.
Keywords: Homeless women -- Services for -- United States; Single mothers -- Services for -- United States; Women's shelters -- United States; Homelessness -- United States; Victims of family violence -- United States